Performance trends in 3000 m open-water age group swimmers from 25 to 89 years competing in the FINA World Championships from 1992 to 2014 - Knechtle, B.; Nikolaidis, P. T.; Rosemann, T.; Rüst, C. A. (Research in Sports Medicine, 2017)
We investigated trends in participation, performance and sex difference in performance in 3000 m freestyle in age groups swimmers (25-29 to 85-89 years) competing in the Fédération Internationale de Natation World Masters Championships between 1992 and 2014. During this period, participation increased in women and men. Women and men improved race times across years in all age groups. Women were slower in age groups 25-29 to 70-74 years. In age groups 75-79 and 85-89 years, however, race times were similar for both women and men. Sex difference in performance remained unchanged across years. In summary, performance improved across years in all age groups, men were faster than women up to the age group 70-74 years and women were not able to reduce the sex difference in performance to men across years. For athletes and coaches, an increase in participation and a continuous improvement in performance can be expected in these age group athletes.